2022
DOI: 10.3171/2021.12.jns212416
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for intracranial chordomas: an international multiinstitutional study

Abstract: OBJECTIVE The object of this study was to evaluate the safety, efficacy, and long-term outcomes of stereotactic radiosurgery (SRS) in the management of intracranial chordomas. METHODS This retrospective multicenter study involved consecutive patients managed with single-session SRS for an intracranial chordoma at 10 participating centers. Radiological and neurological outcomes were assessed after SRS, and predictive factors were evaluated via statistical methodology. RESULTS A total of 93 patients (56 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Such doses are considerably higher than those needed to control skull base meningiomas or schwannomas. [38][39][40][41] Additionally, in a recent multicenter study, Pikis et al 42 investigated the impact of SRS on chordomas and found that a marginal dose > 17 Gy had a protective value in the univariate analysis but not the multivariate analysis. These authors also found that a maximal dose > 29 Gy provided a 24% decrease in the likelihood of neurological deterioration and a 40% decrease in the likelihood of tumor progression.…”
Section: Srs Treatment Outcomesmentioning
confidence: 99%
“…Such doses are considerably higher than those needed to control skull base meningiomas or schwannomas. [38][39][40][41] Additionally, in a recent multicenter study, Pikis et al 42 investigated the impact of SRS on chordomas and found that a marginal dose > 17 Gy had a protective value in the univariate analysis but not the multivariate analysis. These authors also found that a maximal dose > 29 Gy provided a 24% decrease in the likelihood of neurological deterioration and a 40% decrease in the likelihood of tumor progression.…”
Section: Srs Treatment Outcomesmentioning
confidence: 99%
“…A recent analysis of 93 patients with small intracranial chordoma who underwent single-session SRS has been published by Pikis et al. [ 24 ] With a mean maximum dose of 34.2 Gy, the LC after 5 years was 54.7%. Notably, the irradiation volume was much smaller than in the prevailing study (mean 8 cc vs. 40.4 cc).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed methods of the study, SRS techniques, and follow-up protocol have been previously defined. 18 Institutional review board approval and patient consents were obtained in all centers for all included patients. The present article, conducted according to the PROCESS guidelines, 19 is a subgroup analysis limited to histologically proven-with brachyury-positive staining-primary clival chordomas in adults.…”
Section: Methods Patient Population and Inclusion Criteriamentioning
confidence: 99%
“…Recently, we published an international multi-institutional study of 93 clival chordomas treated with SRS at 10 participating centers. 18 The report examined the impact of chordoma SRS for various indications—primary SRS without resection, adjuvant SRS after resection, boost SRS after FRT, and salvage SRS after recurrence. Data are available on reasonable request.…”
Section: Methodsmentioning
confidence: 99%